Study to compare between paperless partogram and modified who partogram in management of labour - Sarojini, Veena L; Sarojini, .; Anagondanahalli, Prathima; Prakash, .; Suchitra, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Partogram is being used since 1954 when Friedman described it for monitoring progress of labour. The Paperless Partogram proposed by Dr. Debdas is a low-skill method for detection of abnormal labour. The main aim of the study is to know efficacy and user friendliness of paperless partogram in comparison with WHO partogram in monitoring and management of labour. Methods: It’s a prospective observational study conducted at Vanivilas hospital where 200 women in labour were included. 6 resident doctors in shifts were asked to fill partograms 100 each for paperless (group A) and WHO (group B). Results: Paperless partogram has scored better than WHO partogram in terms of documentation, learning, time for data entry, cost effectiveness and monitoring of labour. Conclusions: In our study paperless partogram was found to be preferred for monitoring of labour.